Communication as a Tool of Crime Prevention and Effective Justice - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
Experiencing a crime has serious negative effects. Participation in the criminal proceedings, appearing as a witness of the victim, answering questions from the authorities is a serious psychological burden and involves reliving the events. If the victim is unable to process the trauma of suffering a crime, if he is not able to get answers to his questions, these will have negative consequences that affect his or her life. Because of our belief in the justice of the world and our insistence on our right to decide over our own lives, the victims do not understand why they have ended up in this situation.However, in the formal procedure there is no way – as this is not its function – to get answers to the questions burning in them. However, alternative techniques – such as mediation used in various mediation procedures or during diversion – can provide an opportunity to lay down psychological burdens and close the case.However, the chapter not only takes into account the psychological characteristics of the victim situation and shows the positive effect of mediated communication with the perpetrator, but also discusses why these solutions can effectively help prevent re-breaking norms.Keywords: victim, offender, well-being, mediation, communication, crime prevention